Identifikasi Kesiapan Sekolah Menengah Muhammadiyah untuk Implementasi Sekolah Siaga Bencana di Kecamatan Wedi Kabupaten Klaten - Ningsih, Yoza Wahyu; Imawati, Nindi Diah; A'dawiyah, Robiatul; Prihastomi, Anas; Gunawan, Gunawan; Widyatmoko, Wahyu (UNIVERSITAS NEGERI MAKASSAR, 2020)
Â Klaten Regency is one of the regencies in Central Java province that has a regional character that is vulnerable to several natural disasters. Two potential disasters that have been known to the wider community, even internationally, are the eruption of Merapi and earthquake. The purpose of this study was to determine the readiness of Muhammdiyah Middle School in the Wedi District of Klaten Regency for the Implementation of the Disaster Preparedness School and to find out the efforts of the Muhammadiyah Middle School in the Wedi District of Klaten Regency to support disaster preparedness in schools. The method of data analysis in this study uses quantitative descriptive analysis. The results of the study showed that the level of readiness of students and teachers of Muhammadiyah Middle School and Muhammadiyah Vocational Schools, especially the high level Wedi sub-district in the sense that the school was ready for the implementation of disaster preparedness schools, even though they did not meet the procedures for disaster preparedness schools. As an effort, these schools still have very little effort in disaster preparedness due to factors in human resources that lack knowledge of disasters.